Redefining Medieval Balaghah Epistemology: Theoretical Transformations In The Syarah and Hasyiyah Traditions - Aang Saeful Milah; Sulistiani Sulistiani; Uum Umaroh Husaeni; Mugiroh Mugiroh; Insan Ramadhan (JURNAL IJ-ATL, 2026)
This study reconstructs the epistemology of medieval Balaghah. Its aim is to deconstruct the Western-centric narrative that labels the era of commentary (commentary tradition) as a phase of intellectual decline (‘ashr al-inhithath). Specifically, this study maps the theoretical transformations in three branches of Balaghah resulting from the integration of formal logic (manthiq). The method used is qualitative with a historical-philosophical approach. The researcher applies Michel Foucault’s theory of the archaeology of knowledge to analyze the corpus of primary texts (turats), ranging from the works of Al-Sakkaki (d. 626 AH), Al-Qazwini (d. 739 AH), to the authoritative commentaries by Al-Taftazani (d. 793 AH) and Al-Jurjani al-Syarif (d. 816 AH). Analysis of six cross-cluster cases reveals a robust conceptual refinement. The Syarah and Hasyiyah traditions are shown to operate as independent internal critical ecosystems through the "wa fihi nazhar" method. The integration of syllogism successfully transformed the concept of rhetoric originally subjective and based on linguistic taste (al-dzauq) into deterministic-universal linguistic rules. This is evident in the formalization of the cognitive conditions of Kalam Insya’ and the tightening of the criteria for Qarinah at the level of rational-certain clarity (al-zhuhur al-'aqli). The theoretical implications of this research call for a historiographical repositioning to dismantle the dichotomy between the literary (adabi) and logical ('ilmi) approaches. Practically, this research recommends reforming the global Arabic rhetoric curriculum to appreciate traditional commentarial texts as the pinnacle of logical-linguistic intelligence.